Дослідження системи передачі різнотипової інформації з буферизацією та витисненням низькопріоритетних заявок - Melikov, A. Z.; Nagiyev, F. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The approximate formulas for calculating the probability of blocking of packets of different types in store-and-forward systems were developed using access strategy and (pushing out) low priority packets. The problem of finding of upper load limit for traffics of different types which meet requirements to quality of service is solved. The results of numerical experiments are given.